Objective General Knowledge: 2750+Chapterwise Questions - Manohar Pandey; PANDEY (Manohar) (New Delhi Arihant Publications India Pvt Ltd, 2021)
1. The entire syllabus has been divided into sections 2. Questions covered in the book contains answers side by side 3. Provides Recent Years' General Studies questions & 4. Authentic and detailed solution have been given as per latest pattern 5. Each chapter contains variety of questions designed on the line of syllabus In order to crack the hard of the competitions one is required have a vigorous preparations and practice of the subjects. Bringing you the updated edition of the "14000 Objective Questions on General Studies" a compendium of objective questions which will significantly improve the knowledge of the aspiring students. This Question Bank focuses on Indian History & Culture, India & World Geography (Env. & Eco), Indian Polity, Indian Economy, General Science, Science & Technology, General Knowledge and Current Affairs, and every section is divided into sub sections. As the title suggest, it contains more than 2750 objective questions covering General Studies subject. With authentic and detailed answers to the questions, aspirants get an insight into the recent examination pattern and the types of questions asked therein. The book is the best preparation material for general studies for UPSC (CSAT), State PCS, CDS, NDA, etc. TOC Indian History, Geography, Indian Polity, Indian Economy, General Science, General Knowledge.
Keywords: General Knowledge